The importance of games in teaching Spanish grammar - Jonikulova, Guljaxon (The Lingua Spectrum, 2024)
This article focuses on the importance of using games in teaching Spanish. The article focuses on the role of games in teaching Spanish. Teaching lessons through activities requires convenient storage and easy access to materials, objects, pictures, toys, games, fragments of conversations and other props. The article provides several examples of games for use in Spanish lessons. The use of these interactive methods in Spanish lessons makes language learning more useful and meaningful. The use of active games in lessons aimed at developing students’ thinking helps to achieve the goal set in the lesson.